Slavery at sea : terror, sex, and sickness in the middle passage - Mustakeem, Sowande' M., 1978- (New Black studies series., 2016)
"Most times left solely within the confine of plantation narratives, slavery was far from a land-based phenomenon. This book reveals for the first time how it took critical shape at sea. Expanding the gaze even more deeply, the book centers how the oceanic transport of human cargoes--infamously known as the Middle Passage--comprised a violently regulated process foundational to the institution of bondage. Sowande' Mustakeem's groundbreaking study goes inside the Atlantic slave trade to explore the social conditions and human costs embedded in the world of maritime slavery. Mining ship logs, records and personal documents, Mustakeem teases out the social histories produced between those on traveling ships: slaves, captains, sailors, and surgeons. As she shows, crewmen manufactured captives through enforced dependency, relentless cycles of physical, psychological terror, and pain that led to the making--and unmaking--of enslaved Africans held and transported onboard slave ships. Mustakeem relates how this process, and related power struggles, played out not just for adult men, but also for women, children, teens, infants, nursing mothers, the elderly, diseased, ailing, and dying. Mustakeem offers provocative new insights into how gender, health, age, illness, and medical treatment intersected with trauma and violence transformed human beings into the world's most commercially sought commodity for over four centuries."--Publisher's description.